2023
DOI: 10.1002/adma.202306686
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Biohybrid Microstructures Enable Transplantation and Vascularization of Microtissues in the Anterior Chamber of the Eye

Hanie Kavand,
Montse Visa,
Martin Köhler
et al.

Abstract: Hybridizing biological cells with man‐made sensors enable the detection of a wide range of weak physiological responses with high specificity. The anterior chamber of the eye (ACE) is an ideal transplantation site due to its ocular immune privilege and optical transparency, which enable superior noninvasive longitudinal analyses of cells and microtissues. Engraftment of biohybrid microstructures in the ACE may, however, be affected by the pupillary response and dynamics. Here, sutureless transplantation of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In addition, it maintained the functional integrity of islet cells. After using the gene-encoded Ca 2+ indicator GCaMP3, it was found that capillary buds and new blood vessels could be formed in the islets within 2–4 days after transplantation under the microscope [ 204 ]. The study establishes a foundation for future biological tissue engineering and biohybrid technology.…”
Section: Application Of Photo-crosslink Hydrogels In Ophthalmologymentioning
confidence: 99%
“…In addition, it maintained the functional integrity of islet cells. After using the gene-encoded Ca 2+ indicator GCaMP3, it was found that capillary buds and new blood vessels could be formed in the islets within 2–4 days after transplantation under the microscope [ 204 ]. The study establishes a foundation for future biological tissue engineering and biohybrid technology.…”
Section: Application Of Photo-crosslink Hydrogels In Ophthalmologymentioning
confidence: 99%
“…The 3D bioprinted pancreatic petals were found to continue the secretion of insulin and neovascularization after transplantation, thereby dropping the plasma glucose concentration in the murine models ( Klak et al, 2023 ). Also, Kavand et al (2023) constructed a microstructure that can hold pancreatic islets in a specific location within the anterior chamber of the eye (ACE) and promote tissue engraftment ( Kavand et al, 2023 ). Chen et al (2022) reported the fabrication of 3D printed mini-capsule device containing islets that can be used for the delivery of islet cells as a treatment of T1D ( Chen et al, 2022 ).…”
Section: Applications Of 3d Printing and 3d Bioprinting In Diabetic P...mentioning
confidence: 99%
“…69,70 Moreover, hydrogels address several critical challenges encountered in islet transplantation, including issues related to host immune response, oxygen supply, and the establishment of adequate vasculature. 71,72 The development of artificial islets benefits significantly from the utilization of hydrogels, combining the intrinsic biological, physical, and chemical properties of both natural and synthetic hydrogels (Table 1). The functional attributes of hydrogels are intricately influenced by several key factors.…”
Section: Generation Of Stem Cell-derived Insulin-secreting Cellsmentioning
confidence: 99%
“…When it comes to the induction of islet organoids, hydrogels serve as a crucial supporting matrix both within scaffold and non‐scaffold structures 69,70 . Moreover, hydrogels address several critical challenges encountered in islet transplantation, including issues related to host immune response, oxygen supply, and the establishment of adequate vasculature 71,72 . The development of artificial islets benefits significantly from the utilization of hydrogels, combining the intrinsic biological, physical, and chemical properties of both natural and synthetic hydrogels (Table 1).…”
Section: Strategies For Engineering Artificial Isletsmentioning
confidence: 99%